KOMUNIKASI PEMBELAJARAN CALISTUNG MELALUI ALAT PERMAINAN EDUKATIF UNTUK ANAK YATIM DAN PUTUS SEKOLAH DI DESA PIDOLI DOLOK, MANDAILING NATAL - Ahmad Salman Farid; Kholidah Nur, Annisa Wahyuni (JOURNAL OF COMMUNITY DEDICATION, 2022)
This community service activity aims to introduce educational game tools to orphans and school dropouts to equip, develop skills, and add insight and get active, creative and fun learning for early childhood. The target for this service is orphans and school dropouts aged 3-6 years, totaling 33 children in Pidoli Dolok Village, Panyabungan District, Mandailing Natal Regency. Implementation of community service activities using learning communication methods in the form of lectures, discussions, micro teaching and making educational game media tools. The presenter provides learning communication in the form of a lecture. Then, discussions were held with participants regarding the Calistung material through Game Tools. At the end, the children will be invited to learn using the Educational Game Tools that have been provided. The output obtained from this activity is that early childhood is assisted in understanding reading, writing and arithmetic material through early childhood games. The results of this activity can also find out who are early childhood children who are not yet capable of calistung and gain knowledge of calistung after participating in this activity.